2018
DOI: 10.1158/2159-8290.cd-18-0224
|View full text |Cite
|
Sign up to set email alerts
|

Dual MAPK/CDK Targeting in Melanoma: New Approaches, New Challenges

Abstract: Dual MAPK and CDK4/6 targeting is an emerging strategy in melanoma, but toxicity and acquired resistance are limitations. In this issue, two groups (Teh and colleagues and Romano and colleagues) show that therapeutic resistance mechanisms converge on the PI3K pathway, and inhibition of this pathway's mediators can overcome this resistance. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Furthermore, survival analysis showed that C2 had a better prognosis than the other subtypes. In the GSEA, in addition to enrichment for immune-related pathways, the C2 subtype was enriched for many pathways closely related to the occurrence, development, and metastasis of cancer, such as apoptosis, cell adhesion, and focal adhesion, as well as JAK-STAT and MAPK signaling pathways (22)(23)(24)(25)(26)(27). Activation point mutations of FGFR3 are found in up to 80% of low-grade and staged urothelial carcinomas (UC) of the bladder (28).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, survival analysis showed that C2 had a better prognosis than the other subtypes. In the GSEA, in addition to enrichment for immune-related pathways, the C2 subtype was enriched for many pathways closely related to the occurrence, development, and metastasis of cancer, such as apoptosis, cell adhesion, and focal adhesion, as well as JAK-STAT and MAPK signaling pathways (22)(23)(24)(25)(26)(27). Activation point mutations of FGFR3 are found in up to 80% of low-grade and staged urothelial carcinomas (UC) of the bladder (28).…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results showed that SGK1 inhibition significantly decreased pERK1/2 (activated form) expression, and there was no significant difference in the total amount between the two groups. Moreover, SGK1i and RAF→MEK pathway inhibitors synergistically repress the ERK1/2 pathway, along with proliferation of RKO and HT29 cells (19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Mechanism 3: Sgk1 May Be the Downstream Target Gene Of Yap Transcriptional Activation Yap Positively Regulates The Downstream Tamentioning
confidence: 97%
“…The MEK inhibitor strategy is also applicable for breast cancer patients receiving inhibitors of CDK4/6 due to exhibiting MAPK‐related resistance to CDK inhibitor therapy (de Leeuw et al, ). In NRAS mutant melanoma patients receiving dual MEK/CDK4/6 inhibitors, acquired resistance to the PI3K effector S6K1 may occur that confers drug resistance (Romano et al, ), requiring convergence of MEK/CDK inhibitors with suppressors of PI3K pathway's mediators such as S6K to overcome this resistance (Sullivan, ).…”
Section: Mapk In Cancer Growth and Drug Resistancementioning
confidence: 99%
“…Class III BRAF mutants are RAS dependent, so they are sensitive to RAS inhibitors, while classes I and II are RAS independent requiring other mechanisms for dissecting MAPK signaling in tumors harboring these mutants (Yao et al, ). BRAF/MEK inhibition is suggested for class I BRAF mutant cancers, and MEK/ERK inhibition is suggested for non‐class I BRAF mutant cancers (Sullivan, ). For BRAF L597S mutant melanoma, dual MAPK suppression with BRAF/MEK inhibitors is promising to improve survival of affected patients (Dankner et al, ).…”
Section: Combination Therapy Is a Promising Strategy For Targeting Mamentioning
confidence: 99%
See 1 more Smart Citation